Neuropeptide Y receptor 1 and galanin receptor 2 (NPY1R-GALR2) interactions in the dentate gyrus and their relevance for neurogenesis and cognition - Beltran-Casanueva, Rasiel; Hernández-García, Aracelis; de Amo García, Paula; Blanco-Reina, Encarnación; Serrano-Castro, Pedro; García-Casares, Natalia; Fuxe, Kjell; Borroto-Escuela, Dasiel O.; Narváez, Manuel (Frontiers in Cellular Neuroscience, 2024)
Introduction This study may unveil novel insights into the interactions between neuropeptide Y receptor 1 (NPY1R) and galanin receptor 2 (GALR2), in the dentate gyrus of the dorsal hippocampus, shedding light on their role in neurogenesis and cognitive functions. Existing literature highlights the potential of these interactions in enhancing learning and memory, yet detailed mechanisms remain underexplored. Methods Utilizing intracerebroventricular injections of GALR2 and NPY1R agonists in Sprague-Dawley male rats, we examined neurogenesis via markers PCNA and DCX, and memory consolidation through the object-in-place task over a three-week period. Results Significant increases in NPY1R-GALR2 co-localization and neuroblast proliferation were observed, alongside enhanced memory consolidation. These findings suggest a synergistic effect of NPY1R and GALR2 activation on cognitive functions. Discussion Our findings may foster the development of novel heterobivalent or multitargeting drugs, affecting NPY1R-GALR2 interaction, and suggest a future pharmacogical strategy for improving learning and memory found in many brain diseases. Further research is encouraged to explore these mechanisms in pathological models.